A Compact High Gain Multiband Bowtie Slot Antenna with Miniaturized Triangular Shaped Metallic Ground Plane - Dayo, Zaheer A.; Cao, Qunsheng; Wang, Yi; Soothar, Permanand; Khoso, Imran A.; Shah, Gulab; Aamir, Muhammad (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper presents a new compact, high gain and multiband planar bowtie slot antenna. The antenna structure comprises of dielectric substrate, copper conducting sheet, fillet triangular-shaped slots, and a chamfered metallic ground plane. The proposed antenna model is fed with the 50 Ω standard grounded coplanar waveguide (GCPW) feedline. The designed antenna is low profile with compact dimensions of 0.379λ×0.186λ×0.012λ at 2.39 GHz frequency. Stable multi-resonant behavior of frequencies is obtained with the material selection, slots dimensions and position. Moreover, the parametric study has been carried out in order to validate the frequency tuning mechanism and impedance matching control. The novelty of designed antenna lies in high performance features which have been achieved with ultra-compact (0.039λ×0.022λ) modified triangular shaped metallic ground plane. The proposed antenna is fabricated and experimentally verified. The antenna key features in terms of return loss, surface current distribution, peak gain, radiation efficiency and radiation patterns have been analyzed and discussed. The designed radiator exhibits the excellent performance including strong current density, peak realized gain of 6.3 dBi, 95% radiation efficiency, wide fractional bandwidth of 39.5% and good radiation characteristics at in-band frequencies. The simulation and measured results are in good agreement and hence make the proposed antenna a favorable candidate for the advanced heterogeneous wireless communication applications.